Експозиційна робота в Харківському історико-краєзнавчому музеї імені Г. Сковороди у перші повоєнні роки (1944–1950) - Дейнеко, С.М. (Сіверщина в історії України, 2020)
Дослідження присвячене маловідомій сторінці історії Харківського історичного музею – експозиційній роботі у 1944–1950 роках. Нами виявлено, що, не дивлячись на труднощі повоєнного життя, колектив закладу спромігся налагодити ефективну діяльність у створенні постійних і тимчасових виставок, а також надавав певну допомогу своїм колегам з інших міст. The study is dedicated to the little-known page of history of Kharkiv historical museum – expositional work in 1944–1950. At the end of August 1943 Red Army set free Kharkiv once again. From September the city reconstruction started, it was planned to restart the work of a string of state institutions including museum. Concurrently with resumption of institution activity and solving various organizational issues, works on creating new expositions in H. Skovoroda Kharkiv museum of local history were started. It appeared owing to reorganization and merger of a string of city cultural establishments. Subsequently, on its basis, after several reformations and renaming M.F. Sumtsov Kharkiv historical museum arose. The first exposition, built by museum staff members for the anniversary of Kharkiv liberation from Nazis, had a title – «Great Patriotic War». It opened its doors for visitors on 23rd August 1944. One more project, in which museum had to take part in 1944, was collaboration with Kharkiv branch of State institute on design of civil construction in working on set of documents for creating Pavilion of captured exhibition on «Dynamo» stadium. It was planned to restore and adapt room of former «Dancing» on «Dynamo» stadium to the Pavilion of captured exhibition. But this idea remained unrealized. Respectively, in 1944, museum was able to implement only one project in the field of creating new expositions. Yet, in 1947 three permanent expositions, «Industrial exhibition» and three temporary expositions were running in museum, what was objectively better than status of establishment in 1943–1945, but it didn`t save the leadership from crushing, sometimes unfair, criticism. And since, in museum in 1947 a struggle for authority began between two groups of staff members, the first was headed by current director S.D. Sereda, the second was leaded by the head of so - cialist construction department M.A. Voevodin. Conflict led to extended check of museum work and dismissal of museum director S.D. Sereda from his position. The new head of museum became M.A. Voevodin. Dramatic changes brought to H. Skovoroda Kharkiv museum of local history year 1950. Soviet Ukraine government within the reformation of museum sector, ordered to repurpose Kharkiv museum of local history to historical. Considering new reality, museum structure was changed. Nature department was eliminated and the following ones were formed: Department of Primitive communal system, Feudalism history, Capitalism history, Soviet period history. It was also resulted in changes of museum expositional work.